GUIDELINES FOR THE DEVELOPMENT OF THE GRASSROOTS ECONOMY THROUGH COMMUNITY ENTERPRISES FOR SOCIETY - Singmatr, Sanook; Memana, Pikul (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This academic article intends to present guidelines for developing the grassroots economy or community economy, that is, conducting various economic activities from the production level to the consumption level. It is a matter of community participation in thinking. action Receiving benefits and joint ownership After studying and analyzing relevant documents, the author would like to present guidelines for developing the grassroots economy through community enterprises for society, consisting of: 1. The role of the government should fully promote and support the operations of community enterprises in the areas of policy, budget, academics, and regulations. law Production factors and related personnel have a duty to support and subsidize, 2. The role of the private sector (private sector). The private sector should play a role in developing the grassroots economy through community enterprises, including supporting, promoting and helping drive Including facilitating various enterprise networks to assist the government. Both are raw materials Factors of production, capital, equipment, and various knowledge In driving policy, 3. The role of civil society should be to drive network expansion and help fill in the limitations of enterprise groups that are still weak in order to be able to drive towards success, and 4. The role of the network of enterprise groups should also be to play a joint role in helping and supporting each other in various fields. for sustainable success.